Value co-creation and appropriation of platform-based alliances in cooperative advertising - Zhang, Lu; Chen, Feng-Wen; Xia, Sen-Mao; Cao, Dong-Mei; Ye, Zhen; Shen, Cheng-Ran; Maas, Gideon; Li, Yi-Meng (Industrial Marketing Management, 2021)
Digital platforms help develop the open value co-creation strategic alliances, reshape traditional B2B relationships, and promote inclusive social innovation. This research explores the nature of coopetition between the digital platform and its participants. The focus is on how the platform-based alliance balances the contradiction between value creation and appropriation. The support evidence derives from a Stackelberg game in the context of cooperative advertising. Either the platform or the participant supporting advertising in the alliance prompts a Pareto improvement for all players. But the increased profit would be mainly occupied by the dominant platform. The incentive mechanism of profit sharing can promote the alliance to co-create value in a sustainable manner. The game illustrates the significance of cooperative relationships to co-create a larger total value and the existence of an unequal win-win relationship in the strategic alliance. The contradictory logic of cooperation and competition can be accommodated in the platform-based alliance. The dynamic coopetition is involved in a partially convergent interest structure and impacted by power asymmetry. The results highlight the balance between the tensions and harmonies through value creation and appropriation. • Social innovation through value co-creation in the platform-based alliance. • The dynamic coopetition to balance the contradictory logic of value creation and appropriation. • An unequal win-win relationship in cooperative advertising. • The partially convergent interest structure is impacted by power asymmetry.
Keywords: Chine; Co-création; Coopération; Coopétition; Innovation inclusive; Planification; Royaume-Uni; Réservé UdeM